The Impact of Technology on Education: Transforming Learning in the Digital Age - La Jaali; Dwiyanto Dwiyanto; Beki Subaeki (Technologia Journal, 2025)
This study aims to analyze the influence of technology on education and the transformation of learning in the digital era. Rapid technological developments have brought significant changes to learning methods and approaches, enabling the creation of more interactive, flexible, and effective learning experiences. The research method used is the Systematic Literature Review (SLR), which was chosen because it is able to present a comprehensive and structured picture of the results of previous studies. The initial stage of the SLR method is to formulate specific research questions, such as how technology influences learning methods in the digital era, the challenges of implementing technology in education, and strategies for optimizing technology in learning. Furthermore, a literature search was conducted on leading academic databases, such as Google Scholar, Scopus, Web of Science, IEEE Xplore, and ScienceDirect, using keywords such as "technology in education," "digital learning transformation," "the influence of technology on learning," and "e-learning and online learning." The results of the study show that the implementation of technology in education has a positive impact, such as increasing interaction, flexibility, and effectiveness of learning. Technologies such as online learning platforms (LMS), multimedia, artificial intelligence, and digital collaboration tools enable independent learning and better interaction between students and teachers. However, there are challenges in implementing technology, such as the digital access gap, low digital literacy, and the risk of reduced social interaction. To overcome these challenges, it is necessary to improve digital infrastructure, digital competency training, and policies for equal access to technology. Government support and collaboration with the technology industry are essential to maximize the benefits of technology in education.